2013
DOI: 10.1590/s0074-02762013000400022
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in the glutamate-rich protein of Plasmodium falciparum field isolates from a malaria-endemic area of Brazil

Abstract: The genetic diversity displayed by Plasmodium falciparum, the most deadly Plasmodium species, is a significant obstacle for effective malaria vaccine development. In this study, we identified genetic polymorphisms in P. falciparum glutamate-rich protein (GLURP), which is currently being tested in clinical trials as a malaria vaccine candidate, from isolates found circulating in the Brazilian Amazon at variable transmission levels. The study was performed using samples collected in 1993 and 2008 from rural vill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Previous studies have reported two GLURP (R2) alleles in Honduras [ 34 ], three in French Guyana [ 35 ] and each four in Colombia [ 36 ] and Brazil [ 37 ] in the area of low endemicity; however in high endemicity areas in Africa and Asia, anywhere from eight in India to twenty GLURP alleles in Sudan were reported respectively [ 18 , 20 , 21 , 38 ]. Current study found eight alleles in Group-A and nine alleles in Group-B, whereas overall ten alleles were found in the total samples compared to eight reported in Orissa [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported two GLURP (R2) alleles in Honduras [ 34 ], three in French Guyana [ 35 ] and each four in Colombia [ 36 ] and Brazil [ 37 ] in the area of low endemicity; however in high endemicity areas in Africa and Asia, anywhere from eight in India to twenty GLURP alleles in Sudan were reported respectively [ 18 , 20 , 21 , 38 ]. Current study found eight alleles in Group-A and nine alleles in Group-B, whereas overall ten alleles were found in the total samples compared to eight reported in Orissa [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…On comparing present sequences with the previously published sequences [ 1 , 40 ], a maximum number of conserved repeat amino acid pairs were found in Group-A (n = 12) compared to Group-B (n = 11) and NCBI sequences (n = 11). Many studies have reported that the conserved repeat sequences were found to vary among the isolates [ 20 , 30 , 37 ]. There were thirteen different types of haplotype found in the entire field samples, while only seven haplotypes were found in NCBI sequences, of which about 50% contained b-a-c-a in the first four positions.…”
Section: Discussionmentioning
confidence: 99%
“…The K1 allelic family was observed to be predominant in a previous drug trial study in the CHT areas of Bangladesh where msp1 and glurp were used as markers. 19 Since polyclonal infection can enhance the crossing between gametes of different clones to generate novel genotypes by meiotic recombination during sexual reproduction in mosquitoes, 5,6,18,26 prevalence of polyclonal infection was evaluated in this study, which was 94.6%. Usually, the prevalence of polyclonal infections ranges from 20% to 30% for areas with hypoendemicity, 50% in hypo/mesoendemic areas to almost 100% in some holoendemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…In msp1, three distinct allelic families have been described: K1, MAD20, and RO33 while in msp2, two allelic families, FC27 and 3D7/IC, have been described. 8,13,18 These markers have been used to distinguish recrudescence from new infections in various drug trial studies 7,11,12 including studies from CHT areas of Bangladesh. 19,20 Though, msp1, msp2, and glurp have been used in a limited approach in drug resistance studies, the parasite population genetic profile has not been assessed systematically in Bangladesh yet.…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristic is the variable number of repeated nucleotides in the GLURP gene, which modifies the size of the gene and the encoded protein. 14 Several studies have associated its allelic variability with geographical location and the intensity of malaria transmission. [15][16][17] Genetic variation has been shown to contribute to reduced acquired immunity in P. falciparum as immunity is essentially strain-specific (Gandhi et al, 2014;Ocholla et al, 2014;Dechavanne et al, 2017).…”
Section: Introductionmentioning
confidence: 99%